PHYTOCHEMISTRY AND STUDY OF ANTIMICROBIAL ACTIVITY OF FRACTIONS OF HYDRO ETHANOLIC EXTRACT OF LECANIODISCUS CUPANIOIDES (SAPINDACEAE) - TOKOUDAGBA, Kossi Jean-Marie Denis; AHOUANSOU, AYIDE C. (My University, 2022)
Lecaniodiscus cupanioides is a plant of the family Sapindadaceae and the genus lecaniodiscus. It is a tree of 9 meters high with strong woody branches with flowers in fascicles in axillary cluster of purplish green color and perfumed with slender petioles. The species is present in tropical Africa from Sierra Leone to Sudan also in Angola to the South of the Democratic Republic of Congo and in Uganda. The species knows multiple uses in traditional medicine. In the form of inhalation, the bark is used to treat headaches, sinusitis, otitis, eye and ear problems. The leaves are reputed to be antibacterial and rubefacient. They are applied on boils, bruises, but are likely to cause burns if left on too long. It is to have scientific evidence of the use of these leaves that we wanted to study the phytochemistry and the anti microbial activity of the fractions of the hydro ethanolic extract of the dried leaves of the plant used in traditional medicine. We prepared the hydro ethanolic extract from the dried powdered leaves of these plants and the yield of crude extract is 20%. We then fractionated the hydroethanolic extract obtained by the liquid-liquid extraction method using successively the following solvents of increasing polarity: cyclohexane, dichloromethane, ethyl acetate, and metanol. The flavonoids and polyphenols were determined by the colorimetric and Folin Ciocalteu methods in these different fractions and then the hydroethanolic extract and the fractions were tested on four reference microbial strains (Esherichia coli ATCC 25922; Salmonella typhi ATCC 14028; Staphylococcus ATCC 25923; Pseudomonas aeruginosa ATCC 27853) The results showedus that the polar fractions are very rich in polyphenols which confirms the results obtained during the phytochemical screnning carried out on the hydro ethanolic extract; and these fractions have a certain antimicrobial activity than the hydro ethanolic extract. The strongest bactericidal activity is observed in the ethyl acetate fraction of the hydro ethanolic extract. This plant could be an alternative in primary care systems for microbial infections
Keywords: Lecaniodiscus cupanioides Polyphenol Minimum Bactericidal Concentration Minimum Inhibitory Concentration.